EFFECT OF CHEMICAL AND BIOLOGICAL SEED TREATMENTS ON GERMINATION PERFORMANCE OF GCH-7 HYBRID CASTOR (RICINUS COMMUNIS L.) - M. I. JAMADAR,; S. S. CHANDRASHEKHAR, (The Bioscan, 2015)
In order to study chemical and biological seed treatments on germination performance of GCH-7 hybrid castor (Ricinus communis L.) an experiment was carried out during 2013 and 2014 in the laboratory facilities of Department of Seed Science and Technology, University of Agricultural Sciences Dharwad, Karnataka, India. Statistical analysis indicated seed priming with 2 per cent CaCl2 solution significantly reduced mean germination time (5.16 and 5.17). Whereas, daily germination index (16.63 and 15.96), coefficient of velocity of germination (0.180 and 0.173), seed germination (94.14 and 94.33 %), seedling root length (16.00 and 16.98 cm), shoot length (13.36 and 14.17 cm), Seedling Vigour Index-I (2764 and 2938), seedling dry weight (174.7 and 176.7 mg) and Seedling Vigour Index -II (16448 and 16668) were significantly improved during both 2013 and 2014 years of experiment respectively, compared to the untreated seeds (7.31 and 7.32, 14.52 and 13.94, 0.137 and 0.132, 87.56 and 87.29 %, 14.58 and 15.71 cm, 11.48 and 12.28 cm, 2282 and 2443, 150.9 and 150.2 cm, 13282 and 13250 respectively), such improved seed germination performance is due to efficient repair of deteriorated seed parts in presence of Ca+ ion.